1991
DOI: 10.1111/j.1365-3032.1991.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Moth sex pheromone adsorption to leaf surface: bridge in time for chemical spies

Abstract: When brussels sprouts leaves were exposed to air passed over a single calling Mamestra brassicae moth, sex pheromone was adsorbed onto'the leaf surface to such an extent that it subsequently elicited behavioural responses in conspecific male moths, as well as in female Trichogramma evanescens, egg parasitoids of M. brassicae. Male moths responded to odour-treated leaves over a short distance (c. 5 cm) in a wind tunnel, but were not attracted at a distance of 1 m. In contrast, sex pheromone adsorbed to and re-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 36 publications
0
41
1
1
Order By: Relevance
“…Indeed, it is possible that females preferentially call for males in a host plant environment. During the calling process, the sex pheromone can adsorb to the leaf surface, as previously demonstrated in moths 25 . The female can then leave a crucial signal to the larvae.…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, it is possible that females preferentially call for males in a host plant environment. During the calling process, the sex pheromone can adsorb to the leaf surface, as previously demonstrated in moths 25 . The female can then leave a crucial signal to the larvae.…”
Section: Discussionmentioning
confidence: 72%
“…A similar preference by Trichogramma spp. has been observed on Brussels sprouts (Noldus et al, 1991) and maize (Gass, 1988;Suverkropp, 1997), and has also been reported for other arthropods (Evans, 1976;Ayal, 1987).…”
Section: Discussionmentioning
confidence: 88%
“…It is possible that species in the hawaiiensis group exploit different cues to locate their hosts, for example cues produced by a stage different than that attacked (infochemical detour sensu, Vet and Dicke, 1992). The strategy based on cues indirectly associated with the host presence appears widespread among parasitoids, which often exploit host semiochemicals from the adult stage (Noldus et al, 1991;Colazza et al, 1999;Fatouros et al, 2005). In the case of solitary bees and wasps, the adult female constructs the nest for the offspring with the aid of her mouthparts; thus it has been suggested that volatiles from the nest under construction, which are contaminated with chemicals associated with female mouthparts, can also be important in localizing suitable hosts (Cusumano et al, 2010).…”
Section: Discussionmentioning
confidence: 99%